VD_FINDINFO AI 377/23 - 138/2024 vom 2. Mai 2024 - VD Tribunal cantonal (2024)
RENTE D'INVALIDITÉ, COMPARAISON DES REVENUS, REVENU SANS INVALIDITÉ, CALCUL, ADMISSION DE LA DEMANDE | 28 LAI, 29 LAI, 16 LPGA